MATHEMATICS
COLLEGE

Answer: The answer is (0,-5) and (0,5)

Answer:

Answer:

(0,-5) and (0,5)

Step-by-step explanation:

MIDDLE SCHOOL

15 = 5(1 - m) - 2(1 - m)

What is the value for m

Answer:

m = -4

Step-by-step explanation:

First you have to deal with the right side of the equation since it's not spread out.

You therefore have to distribute (in order)

5×1= 5,

5×-m= -5m

And

-2×1 = -2

-2×-m = 2m

Now set it up in the order it was at first (not necessary, but helpful)

15 = 5-5m-2+2m

Add the common values...

5-2= 3

-5m+2m= -3m

Your equation should now look like this:

15= 3-3m

At this point you need to get the common values on the same side, so you would subtract 3 from both sides

15-3= 12

3-3= 0

Since you the 3 cancelled out on the right side, your equation now looks like this:

12= -3m

(Or -3m= 12)

At this point you only need to get m by itself so you would divide by -3 on both sides

-3m/-3= m (or 1m: m is understood as such)

12/-3= -4

The final answer should be

m = -4

Your mom.............................?

Honestly, I don’t know this math ;-;

Honestly, I don’t know this math ;-;

MIDDLE SCHOOL

Which two numbers have a sum of 15 and a product of 36

Answer:

3 and 12

Step-by-step explanation:

let the 2 numbers be x and y then

x + y = 15 → (1)

xy = 36 → (2)

From (1) : y = 15 - x → (3)

substitute y = 15 - x into (2)

x(15 - x) = 36

15x - x² = 36 ( subtract 36 from both sides )

15x - x² - 36 = 0 ( multiply through by - 1 and arrange in standard form )

x² - 15x + 36 = 0 ← in standard form

(x - 3)(x - 12) = 0 ← in factored form

equate each factor to zero and solve for x

x - 3 = 0 ⇒ x = 3

x - 12 = 0 ⇒ x = 12

substitute these values into (3) for corresponding value of y

x = 3 → y = 15 - 3 = 12

x = 12 → y = 15 - 12 = 3

Hence the 2 numbers are 3 and 12

COLLEGE

HELP URGENT - put 27 points on question please help! Write a quadratic function in standard form whose graph passes through (-5,0), (9,0), and (8, -39).

f(x) =

Answer:

f(x) = 3x² - 12x -135

Step-by-step explanation:

standard form of a quadratic equation is

y = Ax² + Bx + C

You are given 3 solutions for X and Y, i.e( x=-5, y = 0), (x = 9,y = 0) and (x = 8,y = -39)

Substitute each of this equations into the quadratic equation to obtain a system of 3 equations

For ( x=-5, y = 0), 25A - 5B + C = 0 ---------- eq (1)

For ( x= 9, y = 0), 81A + 9B + C = 0 ---------- eq (2)

For ( x= 8, y = -39), 64A + 8B + C = -39 ---------- eq (3)

You have 3 equations and 3 unknowns. Solving this system of 3 equations will give:

A = 3, B = -12, c = -135

Hence the quadratic equation is

y = 3x² - 12x -135

or in function form:

f(x) = 3x² - 12x -135

HIGH SCHOOL

Why is it that if you multiply a negative imaginary number (-i) by a positive imaginary number (i), it equals to positive 1? Shouldn’t it be a negative 1? -(-1) • (-1) = -1

This is the right equation, right?

Once we multiply the negative imaginary number (-i) to the positive imaginary number (i),

Which is equal to 1.

so multiply a negative imaginary number (-i) by a positive imaginary number (i), it equals to positive 1.

Hi there!

Unfortunately, that's not the right equation. I'll help show you the proper steps.

So, first, let's define i.

i = √(-1)

Now, let's multiply -i and i

(-i)(i)

Substitute the value of i

- √(-1) * √(-1)

Let's add a parenthesis using the associative property of multiplication

- [ √(-1) * √(-1) ]

Multiplying two same square roots eliminates the square root symbol.

- (-1)

A negative of a negative is positive

= 1

Thus, a negative imaginary number multiplied with a positive imaginary number equals positive 1.

Have an awesome day! :)

Unfortunately, that's not the right equation. I'll help show you the proper steps.

So, first, let's define i.

i = √(-1)

Now, let's multiply -i and i

(-i)(i)

Substitute the value of i

- √(-1) * √(-1)

Let's add a parenthesis using the associative property of multiplication

- [ √(-1) * √(-1) ]

Multiplying two same square roots eliminates the square root symbol.

- (-1)

A negative of a negative is positive

= 1

Thus, a negative imaginary number multiplied with a positive imaginary number equals positive 1.

Have an awesome day! :)